2017
DOI: 10.1080/08039488.2017.1385850
|View full text |Cite
|
Sign up to set email alerts
|

The relationship betweenToxoplasma gondiiIgG antibodies and generalized anxiety disorder and obsessive-compulsive disorder in children and adolescents: a new approach

Abstract: This study shows that serum toxoplasma IgG positivity indicating previous toxoplasma infection increased the risk of GAD 4.171-fold and the risk of OCD 4.846-fold in children and adolescents. Further studies are now needed to investigate the relation between T. gondii infection and GAD/OCD and to determine the pathophysiology involved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 51 publications
0
35
0
Order By: Relevance
“…After reading the full text of the articles, 12 papers were included in our systematic review [1416,1921,2429]. Eventually, 11 of these 12 articles [1416,1921,24,25,2729] were entered into this meta-analysis with respect to the inclusion/exclusion criteria (Fig 1). One of the papers was excluded due to the lack of detailed information about the number of patients with OCD [26].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After reading the full text of the articles, 12 papers were included in our systematic review [1416,1921,2429]. Eventually, 11 of these 12 articles [1416,1921,24,25,2729] were entered into this meta-analysis with respect to the inclusion/exclusion criteria (Fig 1). One of the papers was excluded due to the lack of detailed information about the number of patients with OCD [26].…”
Section: Resultsmentioning
confidence: 99%
“…The total number of participants involved in the 11 included studies in the meta-analysis was 9873, including 389 OCD patients and 9484 controls. Studies were conducted in Turkey [14,16,25], Czech Republic [15,19,21], China [27,29], USA [20], Mexico [28], Saudi Arabia [24], and Iran [26]. Anti- Toxoplasma antibodies (IgG and IgM) were determined using enzyme-linked immunosorbent assay [1416,19,20,2429], indirect immunofluorescence assay [14], complement fixation test [15,19], and enzyme immunoassays [26].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As for TS, an association of OCD with other pathogens cannot be excluded. Apart from case reports of concurrent Mycoplasma pneumoniae or varicella zoster virus infections (67,68) in OCD, an association with a 2.5 to 4-fold increased seroprevalence of antibodies to T. gondii (69) has been reported (70,71). At best, however, this anecdotal evidence suggests a proneness to comorbidity with a broad range of infections, similar to what observed for TS.…”
Section: Postnatal Exposuresmentioning
confidence: 92%
“…T. gondii is also linked to OCD [14,54,63,145] (Table 4). A recent study found that the presence of anti- Toxoplasma gondii IgG (immunoglobulin G) in serum was more frequent in OCD patients than in controls (the odds ratio (OR) was 4.84 (confidence intervals = 1.78–13.12) in favor of OCD) [52] (Table 4). Furthermore, in a 1991 study, Strittmatter and colleagues showed that the CNS areas most affected by T. gondii were the cerebral hemispheres (91%) and the basal ganglia (78%) which are implicated in OCD neurobiology [146].…”
Section: Infections and Ocdmentioning
confidence: 99%